Las Turas dance (Mayéutica Revista Científica de Humanidades y Artes, 2017)
Orlando Pérez is a renowned barquisimetano photographer who has been dedicated to the lens art in the region for more than three decades. The images that we present are part of the series "Danza Las Turas", that Perez made in 2000, about this traditional cultural expression that takes place annually in the Urdaneta municipium of Lara state. "Jesus Christ", as he is affectionately known in the artistic medium, and who is one of the few "analogical photographers" who still resist change, has presented his work in more than 30 solo and group exhibitions in Lara and the rest of the world. country. He has been the winner of the Ecological Art Salon of the Yacambú University (1997 and 1999), IX Hector Rojas Meza Hall of the Ateneo de Cabudare (1999) and Special Mention of the Salvador Valero Hall of the Trujillo State (2008 and 2013).
Keywords: danzas de las turas; culture; tradition